Analytical Assessment of Cadmium, Lead and Iron in Hand Dug Wells of Ilaro, South-Western Nigeria (Global Journal of Science Frontier Research, 2012)
The levels of selected heavy metals; Cadmium, Lead and Iron in the hand dug wells of Ilaro town was critically assessed at strategic points of the area to determine the level of pollution caused by anthropogenic activity within the town using different physical and chemical processes. The Mean ± S.D of the results obtained are; Cadmium 0.017±0.016 mg/l; Lead 0.229±0.061 mg/l; Iron 1.076±2.393 mg/l. All the parameters were higher than the standards that were specified for drinking water by WHO. Consequently, the well water in the study location is not suit for drinking.
Keywords: Ilaro; Heavy metals; Pollution; Metal; Water quality; Contaminants